Determinan Minat Individu Menjadi Pengemudi Kendaraan Online - Ervilia Agustine Wiharsianti; Kahfi Fikrianoor; Listia Nur Aini; Amir Hidayatulloh (Jurnal Manajemen, 2020)
AbstractThis research is a type of qualitative research with primary data types. The purpose of this research is to find out the factors that influence individuals to become vehicle drivers online. The population of this study is online drivers. The sampling technique from this study uses convience sampling. Collecting data in this study by conducting interviews with onlime vehicle drivers. Respondents in this study amounted to 10 respondents. This study obtained the results that perceived behavior control, subjective norms, and attitudes toward behavior are factors that influence individuals to become vehicle drivers online.Keywords: perceived behavior control, subjective norms